Detection of flubromazolam in patients with suspected non-medical drug use attending emergency departments in the United Kingdom. (2nd January 2022) - Haden, Mark; Cashman, Josephine; Ketchin, Andrew; Macfarlane, Rebecca; Issa, Shabana; Eddleston, Michael; Hines, Selina; Hudson, Simon; Hill, Simon L.; Thomas, Simon H. L.
Abstract: Introduction: Non-medical use of novel benzodiazepines has recently become common. Here, we describe the recent frequent detection of flubromazolam in patients attending United Kingdom emergency departments. Methods: Adults presenting to participating hospitals with toxicity after suspected drug misuse were studied between March 2015 and January 2021. Clinical features were recorded using consistent methodology and biological samples analysed using liquid chromatography–tandem mass-spectrometry. Results: Flubromazolam and/or its mono-hydroxylated metabolite were detected in samples from 14 of 957 patients, all presenting since July 2020. Reported clinical features included reduced level of consciousness (10), confusion/agitation (6) and acidosis (5) but multiple other substances were detected in all patients. All patients survived to discharge (length of hospital stay 3.0 to 213 h, median 24.1 h). There was no correlation between admission blood/serum flubromazolam concentrations (range 1.7–480.5 ng/ml, median 7.4 ng/ml) and Glasgow Coma Scale or length of hospital stay. In one patient who needed intubation and ventilation for five days, there was an exponential decline in flubromazolam concentrations with time (calculated half-life 39.8 h). Hydroxyl-flubromazolam was also identified at all time points. Conclusions: Flubromazolam has been detected frequently in drug users presenting to UK emergency departments since July 2020. Prolonged toxicity may occur as a result of the long half-life of flubromazolam and the production of metabolites likely to be active.